Treatment of alcohol dependence in Swedish primary care: perceptions among general practitioners - Karin Hyland; Anders Hammarberg; Sven Andreasson; Maria Jirwe (Taylor & Francis Group, 2021)
Objective To describe general practitioners' (GPs) attitudes to the management of patients with alcohol dependence in primary care and current treatment routines and their view on a new treatment approach; internet-based Cognitive Behavioral Therapy (iCBT). Design A qualitative interview study with ten GPs participating in a randomized controlled trial. The interviews were analyzed using qualitative content analysis. Setting The participating GPs were recruited via purposeful sampling from primary care clinics in Stockholm. Subjects The GPs were participants in an RCT investigating if iCBT when added to treatment as usual (TAU) was more effective than TAU only when treating alcohol dependence in primary care. Results The GPs found alcohol important to discuss in many consultations and perceived most patients open to discuss their alcohol habits. Lack of training and treatment options were expressed as limiting factors when working with alcohol dependence. According to the respondents, routines for treating alcohol dependence were rare. Conclusion GPs believed that iCBT might facilitate raising questions about alcohol use and thought iCBT may serve as an attractive treatment option to some patients. The iCBT program did not require GPs to acquire skills in behavioral treatment, which could make implementation more feasible.KEY POINTS Alcohol dependence is highly prevalent, has a large treatment gap and is relevant to discuss with patients in many consultations in primary care. This study is based on interviews with 10 GPs participating in a randomized controlled trial comparing internet-based Cognitive Behavioral Therapy (iCBT) for alcohol-dependent patients to treatment as usual. GPs viewed alcohol habits as important to discuss and they perceived most patients are open to discuss this. The access to iCBT seemed to increase GPs' willingness to ask questions about alcohol and was viewed as an attractive treatment for some patients. The iCBT program did not require GPs to acquire skills in behavioral treatment, which might be timesaving and make implementation more feasible.